FACTORS CONTRIBUTING TO HIGH δ13C VALUES IN CRYOGENIAN LIMESTONES OF WESTERN MONGOLIA - Shields G.A.; Brasier M.D.; Stille P.; Dorjnamjaa D.-I. (My University, 2002)
A geochemical study of Cryogenian (late Neoproterozoic) limestones from western Mongolia is presented, including δ13C (carbonate and kerogen), δ18O, 87Sr/86Sr and rare earth element data. Carbon isotope compositions confirm the existence of anomalously high δ13C in Cryogenian seawater with δ13Ccarb>+10‰. Positive δ13C excursions are explained conventionally by elevated rates of organic carbon burial. However, four additional factors appear likely to have contributed to δ13C excursions during the Cryogenian: (1) increased δ13C of carbon input (δi) due to the exposure and weathering of carbonate platforms during sea-level falls, (2) increased carbon isotopic discrimination between carbonates and organic carbon (Δδ13C) due to microbial reworking of primary organic matter, (3) locally elevated δ13C in restricted basins and (4) enhanced vertical gradients in seawater δ13C due to redox stratification. All four factors may have contributed to similar positive δ13C excursions at other times, and may help to explain the almost ubiquitous association of eustatic regression, and cooling, with high δ13C during the late Neoproterozoic and early Palaeozoic.
Keywords: Cryogenian; Precambrian::Proterozoic::Neoproterozoic::Cryogenian; Докембрий::Протерозой::Неопротерозойская::Криогений